Micro-magnetic analysis of friction stir welded steel plates - Raja A.R.; Khan Yusufzai M.Z.; Vashista M. (My University, 2025)
Present work aims to assess the applicability of Barkhausen noise technique for assessment of friction stir weld characteristics. Steel plates (IS-2062 grade) were joined using friction stir welding process at various tool rotational speeds (550 to 700 rpm) while other parameters were kept constant. As-received material and welded steel plates were characterized using Barkhausen noise technique, metallographic inspection, and micro-hardness testing. Friction stir welding resulted in grain refinement which leads to higher hardness in all welded samples in comparison to the base metal. The nature of residual stress as obtained from X-ray diffraction analysis was compressive. Compressive residual stress and higher hardness in welded samples clearly depicted changes in Barkhausen noise signal profiles in terms of peak amplitude and peak position. Variation in root mean square value of Barkhausen noise signal is explained in terms of induction of compressive residual stress and microhardness. © 2018, Springer-Verlag London Ltd., part of Springer Nature.